Role of Creative Thinking in Assessment Techniques Among University Students (Journal of Asian Development Studies, 2023)
This study explores assessments' crucial role in encouraging people to improve their critical and creative thinking abilities. A critical skill for managing today's complicated and fast-changing world is the ability to think creatively. Assessment of these talents becomes crucial in guiding successful educational practices as educators and researchers work to improve creative thinking abilities. The study employed a survey approach and was quantitative. Students from district Lahore universities made up the study's population. One hundred fifty students from district Lahore's public and private institutions made up the study's sample. Data gathering involved the use of a questionnaire. Two components comprised the questionnaire: the first portion contained demographic data, while the second contained assessment methods. Descriptive statistics was used for data collection. The value of creative thinking in many personal, intellectual, and professional situations is established in the first paragraphs of the essay. It highlights how creative thinking has several facets, including ideation, problem-solving, originality, and adaptation.